DOA estimation method for time-varying metasurface based on asynchronous modulation - YI Ming; CHEN Ming; ZHONG Zhou; JIN Liang (Dianxin kexue)
In response to the challenge of spectral aliasing in target signals, which arose from constraints on the temporal modulation rate in existing time-domain direction of arrival (DOA) estimation methods, a novel asynchronous control-based DOA estimation technique was proposed. This approach significantly increased the modulation rate, effectively mitigating the problem of spectral aliasing and consequently broadening the signal processing bandwidth. This novel approach capitalized on the inherent persistence of unit states over a duration, without necessitating any alterations to the hardware constraints of the time-varying metasurface (TVM). By staggering the initiation of state changes across various column units, the method enabled the acquisition of multiple distinct responses within a single state’s temporal window. The asynchronous modulation strategy effectively augmented the virtual channel count under the limitations imposed by material properties, thereby enhancing the precision of DOA estimation. Empirical simulation outcomes substantiated the efficacy of this approach, demonstrating a significant enhancement in DOA estimation performance compared to existing synchronous modulation techniques, closely approximating the theoretical optimum for DOA estimation outcomes.